Occupational and demographic factors associated with drug use among female sex workers at the China–Myanmar border. (1st April 2016) - Hail-Jares, Katie; Choi, Sugy; Duo, Lin; Luo, Zhi; Huang, Z. Jennifer
Highlights: Occupational and personal relationships impacted Burmese sex workers drug use. Specifically, client specialization was strongly associated with current drug use. Both drug using and non-drug using FSW used condoms at high rates. Yet drug using FSW were more likely to report a STI diagnosis. Health interventions should empower FSW to manage client-driven drug use. Abstract: Background: Within the last decade, the use of amphetamine type stimulants (ATS) has swelled in Myanmar. Regionally, female sex workers have reported turning to ATS for occupational reasons. In doing so, drug-using female sex workers (FSW) face compounded risks for HIV and other sexually transmitted infections (STI). Here, we examine the factors that impact FSW drug use in Muse, a town along the China–Myanmar border. Methods: In 2012, 101 FSW were recruited from entertainment venues and brothels along the Myanmar–Chinese border. Participants participated in a self-administered behavioral survey covering demographics, drug use, sex work, and risk behaviors. Bivariate and regression analyses were conducted in SPSS. Results: Thirty four percent of respondents indicated current drug use. ATS derivatives were the most commonly used drugs (87.5%) with injection drug use being nearly non-existent in the sample. Drug using FSWs were older, had engaged in sex work longer, had more Chinese clients, and were more likely to have a previous boyfriend who had used drugs. They were also 3.5 times more likely to report a STI. Client condom use, HIV testing rates, and familiarity with public health resources did not statistically differ by drug use status. Conclusion: More research is needed to examine how romantic and professional sexual relationships push-and-pull FSW into using drugs. Our results suggest that diverse safer sex strategies, beyond client condom use, should be promoted with drug using FSWs, including strategies that acknowledge the impact of ATS use.